Incidencia e importancia de la prueba de rotavirus en niños menores de dos años con diarrea para el diagnóstico de EDA que acuden al hospital Alfonso Villagómez Román en el período diciembre 2015 - mayo 2016. - Barahora Basantes, Patricia del Pilar (2016)
Acute diarrheal disease is the most common of deaths of children under two years cause. Diarrhea can last several days and may deprive the body of water and salts necessary for survival. According to the OMS (World Health Organization) cause the death of 760000 million children each year. One of the most common causes of diarrhea is rotavirus infection this being a virus that affects a large extent to children as it is transmitted via fecal gold and children are exposed. That's why this paper also talks about the importance of clinical laboratory test is a method for the in vitro qualitative detection of Rotavirus antigen in stool. Rotavirus can easily spread. Good hand hygiene (hand washing) and cleanliness are important measures to prevent the transmission of this virus. In the six months of research that is in the period December 2015 - May 2016 at the Hospital Alfonso Villagomez Roman city of Riobamba there is a 10% positive rotavirus corresponding to 77 children / as with diarrhea, having a greater impact on male gender with 53%. Exploratory-descriptive research is used, field research and documentary field because data is collected directly from reality and documentary information gathered by surveys mothers and is also a cross-sectional study for a period of time was six months was defined.